2007
DOI: 10.21914/anziamj.v47i0.1078
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of students for tertiary studies requiring mathematics

Abstract: Mathematics education in Queensland seems to be on a neverending downwards spiral. This is the opinion of the majority of the staff in the School of Maths and Physics at James Cook University. Over recent years the staff in our School have struggled to output students at a standard third year tertiary mathematics level. There are two reasons for this: firstly the intake is from a less well prepared student body and secondly, perhaps more critically, the indicators used to measure the ability of secondary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…We suspect that given the content of the Mathematics B and C curricula described in , having a working knowledge of calculus and algebra offers a technical advantage and promotes the higher‐order logical skills necessary to succeed in these particular tertiary studies. This is consistent with the findings of Belward et al. (2007) who highlight algebra and calculus as the key missing components in students’ secondary mathematics education.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We suspect that given the content of the Mathematics B and C curricula described in , having a working knowledge of calculus and algebra offers a technical advantage and promotes the higher‐order logical skills necessary to succeed in these particular tertiary studies. This is consistent with the findings of Belward et al. (2007) who highlight algebra and calculus as the key missing components in students’ secondary mathematics education.…”
Section: Discussionsupporting
confidence: 92%
“…Some authors have sought to measure the ‘mathematics effect’ by performing empirical studies, based on their own tests, relating to the presence of basic mathematics skills in undergraduates taking business (Standing, 2006; Standing et al ., 2006), education (Peard, 2004), economics (Ballard and Johnson, 2004) and mathematics itself (Belward et al ., 2007), and how these affect performance at university. With the exception of Peard (2004), these studies have found that newly enrolled undergraduates’ mathematics skills were inadequate for the subjects they elected to take.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numeracy has been shown to influence the performance of rst year students (Maris and Jacobs, 1995;Alcock et al, 2008) and that students without a maths prerequisite are less prepared for tertiary study (Ballard and Johnson, 2004;Standing, 2006;Belward et al, 2007;Rainsbury and Darroch, 2009). This paper examines whether conducting a mathematical aptitude test ('maths quiz') in orientation week, followed by offering students a workshop program ('maths workshop') to develop (or in some cases refresh) their maths skills influences their performance in a 1 st year course.…”
mentioning
confidence: 99%